Occupational Pesticide Exposure and Reduced eGFR in Farmers - Hansen Hansen; Mursid Raharjo; Suhartono Suhartono; Nur Endah Wahyuningsih (Poltekkes Kemenkes Surabaya, 2026)
Pesticides are frequently utilized in modern farming to sustain crop productivity. However, improper use may pose occupational health risks, including chronic renal toxicity. In Indonesia, evidence regarding long-term kidney effects among farmers remains limited. This study aimed to determine the prevalence of reduced estimated glomerular filtration rate (eGFR) and examine its association with pesticide exposure among horticultural farmers in Wanasari District, Brebes Regency. A cross-sectional analytical study was conducted among 367 farmers aged 18-63 years. Data on pesticide use, personal protective equipment (PPE), smoking habits, health complaints, and hypertension were collected through interviews. Serum creatinine levels were measured enzymatically and used to estimate eGFR. Multivariate logistic regression analysis was applied to identify factors associated with reduced renal function. Several variables showed a significant association with decreased renal function, namely smoking status (OR = 2.972; 95% CI: 1.299-6.001; p = 0.009), pesticide dosage (OR = 4.555; 95% CI: 2.415-8.291; p < 0.001), PPE use (OR = 0.383; 95% CI: 0.199-0.737; p = 0.004), health complaints (OR = 2.972; 95% CI: 1.567-5.636; p = 0.001), hypertension (OR = 2.367; 95% CI: 1.278-4.382; p = 0.006), working period (OR = 15.057; 95% CI: 3.510-64.591; p < 0.001). Working period was the dominant factor associated with decreased kidney function in farmers. This indicates the importance of chronic exposure duration in increasing the risk of pesticide-induced nephrotoxicity. Prevention efforts should focus on controlling exposure duration, improving adherence to PPE use, providing education on pesticide use, and regularly monitoring kidney function.